2021
DOI: 10.1080/00423114.2021.2013506
|View full text |Cite
|
Sign up to set email alerts
|

Novel high-fidelity tyre model for motorcycles to be characterised by quasi-static manoeuvres – rationale and numerical validation

Abstract: Although diverse tyre model formulations exist in literature, they are suited for characterisation using a dedicated test bench, preventing parameters' estimation in driving conditions.This study defined a novel motorcycle tyre model, characterisable through driving manoeuvres using simple instrumentation consisting in an inertial measurement unit, steering position sensor and wheel speed sensors. Acquired signals were used to estimate instantaneous tyre forces, moments, slip angle and other properties, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The authors assumed as valid the empirical flux variation law, presented in [46] and reported in Figure 15, derived from previous experimentation. To assess the actual influence of this parameter, it is necessary to make a complete vehicle model, evaluating suspension displacement and tyre reaction model, developed both for automotive and motorcycle applications (see [50], [51]). In this case, air gap, shown in Figure 16 has been considered constant during the test, assuming a smooth driving (constant speed) with no emergency brakes.…”
Section: Physical Modelmentioning
confidence: 99%
“…The authors assumed as valid the empirical flux variation law, presented in [46] and reported in Figure 15, derived from previous experimentation. To assess the actual influence of this parameter, it is necessary to make a complete vehicle model, evaluating suspension displacement and tyre reaction model, developed both for automotive and motorcycle applications (see [50], [51]). In this case, air gap, shown in Figure 16 has been considered constant during the test, assuming a smooth driving (constant speed) with no emergency brakes.…”
Section: Physical Modelmentioning
confidence: 99%
“…Tyre forces are a linear combination of tyre slip and camber, including a relaxation behaviour; tyre moments due to turnslip and pneumatic trail are neglected. Tyres are lenticular, leading to lower roll angle values than toroidal wheels [18] unless an overturning moment is included separately [19]. This aspect influences the simulation because the lower roll angle causes lower camber angles and, thus, lower camber thrust, so the slip angles have to change to maintain equilibrium.…”
Section: High-fidelity and Simplified Motorcycle Modelsmentioning
confidence: 99%
“…For the single-track model, the yaw rate ψ is defined as the angular speed around the axis perpendicular to the ground; this is not the case for BikeSim © or most experimental data, where the yaw rate measured by the Inertial Measurement Unit is expressed in the tilting motorcycle frame. In such case, the measured yaw rate measured must be converted into the one relative to the vertical axis [19]:…”
Section: Transient Conditionsmentioning
confidence: 99%
“…The longitudinal and lateral tire forces of the i-th (i = 1, 2, 3, 4) driven wheel are characterized using the empirical model [34], [35] as:…”
Section: A Vehicle Planar Dynamicsmentioning
confidence: 99%